2011
DOI: 10.1002/qua.23030
|View full text |Cite
|
Sign up to set email alerts
|

Isatin‐Schiff base copper(II) complexes—A DFT study of the metal‐ligand bonding situation

Abstract: Herein, we report results of calculations based on density functional theory (BP86/TZVP) of a set of isatin-Schiff base copper(II) and related complexes, 1-12, that have shown significant pro-apoptotic activity toward diverse tumor cells. The interaction of the copper(II) cation with different ligands has been investigated at the same level of theory. The strength and character of the Cu(II)-L bonding was characterized by metal-ligand bond lengths, vibrational frequencies, binding energies, ligand deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 90 publications
0
14
0
3
Order By: Relevance
“…The quantum calculations, in particular density functional theory (DFT), are widely used in coordination chemistry not only to achieve a quantitative description of * Corresponding author. Email: sa_zarei@iausdj.ac.ir, Seyedamirzarei@yahoo.com chemical and physical features of different complexes but also to predict new physical and chemical features [16][17][18][19][20][21]. Rigamonti et al reported the DFT calculation of the copper complexes of some salen-type ligands to confirm the assignments of electronic absorption spectra and evaluate the NLO properties [22].…”
Section: Introductionmentioning
confidence: 96%
“…The quantum calculations, in particular density functional theory (DFT), are widely used in coordination chemistry not only to achieve a quantitative description of * Corresponding author. Email: sa_zarei@iausdj.ac.ir, Seyedamirzarei@yahoo.com chemical and physical features of different complexes but also to predict new physical and chemical features [16][17][18][19][20][21]. Rigamonti et al reported the DFT calculation of the copper complexes of some salen-type ligands to confirm the assignments of electronic absorption spectra and evaluate the NLO properties [22].…”
Section: Introductionmentioning
confidence: 96%
“…They are corroborated by the corresponding DFT-obtained EPR parameters, that indicate a square planar geometry around the metal for all the compounds except for [Cu(isaepy) 2 ] which shows an octahedral geometry with a z axis longer than the others. Differences between the DFT-obtained EPR parameters explored by Caramori et al 20 and the experimental results may be related to the matrix influence on the g-tensors, which was not taken into account during the simulation.…”
Section: Epr-based Structural Data and Antiproliferative Activities Of Copper(ii) Compoundsmentioning
confidence: 95%
“…Figure 2 shows the DFT-optimized structures evaluated in previous investigations. 20 Two functionals, namely BPW91-35 and BPW91-60, were evaluated to understand the influence of spin density and EPR parameters on the combination of exact exchange in hybrid functionals, as previously studied by Kaupp. 24 BP86 was shown to produce underestimated g || values.…”
Section: Dft Methods As a Theoretical Support For Epr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The topological analysis of the electron density realized through of the QTAIM method shows the existence of bond critical points (BCPs) between the receptors (1-10) and the anion F -, which point to bonding interactions. 39,40 The main molecular graphs have been organized in the Figure 3, while similar representations have been put in the Figure S3. The ratio between the kinetic energy density, Gb, and the potential energy density, Vb, -Gb/Vb, and the electron density, ρb, in the main BCPs of the complexes (1-10) ….…”
Section: Articlementioning
confidence: 99%